2007
DOI: 10.3989/gya.2007.v58.i4.447
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of carrot seeds (<i>Daucus carota</i> L.) cultivated in Turkey: characterization of the seed oil and essential oil

Abstract: RESUMENComposición química de semillas de zanahoria (Daucus carota L.) cultivadas en Turquía: caracterización del aceite de semilla y del aceite esencial.Se determinó la composición química y las propiedades físicas de las semillas de zanahoria (Daucus carota L.) obtenidas en Konya, Turquía, con objeto de investigar usos potenciales de las mismas. Se determinó la humedad, el peso, el contenido proteico, en aceite, en fibra, en ceniza, en ceniza insoluble en ácido clorhídrico, los carbohidratos totales, y el re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 33 publications
1
12
0
2
Order By: Relevance
“…Carotol was determined as the main compound in the essential oil of cultivated D. carota from Turkey. Also, limonene was found in a low amount (0.4%) and elemicin was not detected in the oil of the previous study [20]. The present study showed that have similar essential oil components to previous studies.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Carotol was determined as the main compound in the essential oil of cultivated D. carota from Turkey. Also, limonene was found in a low amount (0.4%) and elemicin was not detected in the oil of the previous study [20]. The present study showed that have similar essential oil components to previous studies.…”
Section: Discussionsupporting
confidence: 76%
“…The wild carrot oil has biological properties such as antimicrobial, hepatocellular regenerator, general tonic and stimulant, cholesterol regulatör, and cicatrizant [6]. The main compounds of oils of D. carota were carotol, sabinene, -pinene, geraniol, β-bisabolene, γ-bisabolene, (E)-methyl isoeugenol, (E)-asorene, daucene and geranyl acetate [6,8]. There are many reports on the essential oil composition of D. carota and F. vulgare in the literature.…”
mentioning
confidence: 99%
“…The inflammatory and anti-carcinogenic activities of various plants, such as anise, chamomile, hops, lavender, coriander, ginger, apples, and carrot seeds, were attributed to the presence of farnesene. More recently, farnesene was shown to have in vitro antioxidant effects [22,23]. β-Pinene (C 10 H 16 ), another one of the major components of the hexane extract, is a monoterpene bicyclic compound present in the vast majority of essential oils that possesses antioxidant activity [21,24].…”
Section: Discussionmentioning
confidence: 99%
“…Такое явление может быть связано с более высоким содержанием эфирных масел в семенах петрушки, сельдерея и пастернака по сравнению с семенами цикория и моркови. В пользу этого указывают высокие показатели антиоксидантной активности и содержания эфирных масел петрушки, пастернака и сельдерея [27][28][29][30] и низкая вариабельность накопления полифенолов семенами указанных культур (рис.1b). Известно, что основными компонентами эфирных масел петрушки с высокой антиоксидантной активностью являются миристицин 34.18%, α-пинен 16.14% и апиол 15.69% [27].…”
Section: таблица 2 общее содержание полифенолов (тр) селена (Se) и уровень общей антиоксидантной активности (аоа) семян цикория петрушки unclassified
“…У семян сельдерея основным компонентом эфирного масла является лимонен [29]. У семян моркови содержание эфирного масла в 3 раза ниже, чем в семенах петрушки, а основными компонентами масла являются каротол (66.78%), дауцен (8.74%) и фарнезен (5.86%) [30].…”
Section: таблица 2 общее содержание полифенолов (тр) селена (Se) и уровень общей антиоксидантной активности (аоа) семян цикория петрушки unclassified